OPTIMIZING BALANCE AND COORDINATION THROUGH INTEGRATED PHYSICAL EXERCISE IN PATIENTS FOLLOWING FRACTURE SURGERY - Nugroho, Rio Kristian; Hasnah, Kholifah (Universitas Kusuma Husada Surakarta, 2025)
Background: The high incidence of traffic accidents has led to a significant increase in fractures, particularly of the lower extremities, many of which require treatment through Open Reduction and Internal Fixation (ORIF) procedures. Post-ORIF patients commonly experience pain and fear in performing daily activities, including impaired balance and coordination. To address this condition, a structured and progressive integrated physical exercise intervention is necessary. This study aims to evaluate the impact of an integrated intervention that combines physical activity, pain management, and enhancement of fall efficacy on the functional status of patients recovering from lower extremity fracture surgery using the Open Reduction and Internal Fixation (ORIF) procedure.Methods: The study was conducted using a pre-experimental design with a single-group pretest-posttest approach to 53 post-ORIF patients with lower extremity fractures treated in the inpatient ward of Sragen Regional General Hospital, Surakarta. Instruments used included the Barthel Index to assess functional status, the Fall Efficacy Scale, and a clinical observation sheet to evaluate physical ability. Data were analysed using the Wilcoxon test.Results: Data showed an improvement in balance function, coordination, and overall functional status in post-ORIF patients with lower extremity fractures after receiving the integrated activity training intervention. The Wilcoxon test showed a p-value of 0.001, indicating a statistically significant effect.Conclusion: The study demonstrates that an integrated physical exercise program combined with pain management and fall efficacy enhancement has a significant impact on improving balance, coordination, and functional status in patients recovering from fractures.